Attendance management system for iOS device based on iBeacon technology - Zhang, Yunlong (2016)
iBeacon is a novel technology which was announced by Apple in 2013. Devices equipped with Bluetooth low energy (BLE), the fourth version of Bluetooth, can be used to build an iBeacon region around an object. This allows an iOS device to record when it has entered or left the region, along with an estimation of proximity to a beacon. In this dissertation project, an attendance management system application for iOS device is developed based on the use of iBeacon technology for attendance analysis. The application can monitor the special advertising signal from iBeacon device to activate its core function, which is determining the time the application enter and leave a region and then used for related data analysis. Since iBeacon technology is a cutting-edge technology that has rapidly developed recently, so far only a few applications are available on Apple App Store with core features of iBeacon. However, by comparing those available applications for attendance analysis, we found out that almost all of them only provide simple situation attendance management such as indoor attendance management. Hence, we decided to develop an application with high mobility, that is to say, this application is suitable for both of indoor and outdoor situations. Furthermore, user can use either iOS device with BLE or just a small iBeacon tag to make their attendance information recorded, which significantly improves the practicality of this application. Additionally, this project applies cloud server to achieve data storage, special users Iike administrator can also manage information through graphical database management software on computer. All of the mentioned features make the whole system work in high performance.